A passivation method for a thermally evaporated perovskite LED light-emitting layer, a perovskite light-emitting layer and an LED device
Patent Information
- Application Number
- CN202311033308.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-08-16
AI Technical Summary
The existing thermally deposited perovskite LED devices have low luminous performance, mainly because the deposited perovskite film is prone to defects, resulting in poor electrical properties. Existing passivation methods, such as Cs4PbBr6 passivation layers, have poor conductivity, which limits the improvement of the device's electroluminescence characteristics.
A CsZnX3 structure phase uniformly passivated and encapsulated CsPbX3 structure phase was prepared by dual-source co-evaporation or interface-induced assisted thermal annealing. By controlling the raw material ratio and evaporation rate, a CsZnX3 passivation layer was formed, where X is one or two of Br, Cl, or I. Combined with interface-induced annealing treatment, a CsZnX3 structure phase uniformly passivated and encapsulated CsPbX3 structure phase was formed.
The CsZnX3 passivation layer not only improves the passivation effect but also enhances conductivity and reduces Pb content, significantly improving the luminous efficiency and current characteristics of LED devices. It also overcomes the effects of Pb toxicity and is simple to operate with good controllability.
Smart Images

Figure CN117096245B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite optoelectronic device technology, specifically relating to a passivation method for thermally evaporated perovskite LED light-emitting layer, the perovskite light-emitting layer, and the LED device. Background Technology
[0002] Lead halide perovskite materials have attracted widespread attention due to their excellent optoelectronic properties, such as large absorption cross-section, high fluorescence quantum efficiency, narrow emission peak, and tunable bandgap, showing significant application prospects in fields such as novel displays, lighting, solar cells, and X-ray detection imaging. Currently, there are two main methods for preparing the emitting layer for perovskite light-emitting diodes (LEDs): solution deposition and thermal evaporation. Among these, the dual-source thermal evaporation method has outstanding advantages such as simple control, good film uniformity, and the ability to fabricate large areas, and it is compatible with existing production line processes, making it the most widely used. However, because the deposited perovskite film is prone to generating numerous defects, affecting the film's luminous efficiency, the luminous performance of current thermally deposited perovskite LED devices is generally low. Research has found that surface passivation treatment of the perovskite emitting layer is one of the effective ways to reduce the defect density of the film and improve its luminous efficiency. Taking CsPbBr3 perovskite as an example, it is typically prepared by dual-source co-evaporation of CsBr and PbBr2. During the evaporation process, by controlling the ratio of CsBr to PbBr2, a Cs4PbBr6 structural phase can be formed, ultimately resulting in a CsPbBr3 phase encapsulated by Cs4PbBr6, thereby achieving passivation of CsPbBr3. However, Cs4PbBr6 has a large band gap and poor conductivity, leading to unsatisfactory electrical characteristics of the device, ultimately limiting further improvements in the device's electroluminescence properties (such as brightness and luminous efficiency). Summary of the Invention
[0003] To address the aforementioned problems in the prior art, this invention provides a novel passivation method for a lead halide perovskite LED light-emitting layer, the light-emitting layer obtained by the passivation method, and an LED device containing the light-emitting layer.
[0004] The object of this invention is achieved in the following manner: A passivation method for thermally vapor-deposited perovskite LED light-emitting layers involves preparing a CsZnX3 structural phase uniformly passivated and encapsulating a CsPbX3 structural phase using a dual-source co-evaporation method or an interface-induced assisted thermal annealing method, where X is one or two of Br, Cl, or I.
[0005] The dual-source co-evaporation method specifically includes the following steps: First, CsX and PbX2 are weighed at a molar ratio of 1.2-4:1 and ground to obtain a uniformly mixed Cs-Pb-X solid powder; then, using Cs-Pb-X solid powder and ZnX2 as raw materials, a dual-source co-evaporation method is adopted, controlling the evaporation rate ratio of ZnX2 to Cs-Pb-X at 1:50~1:5, the evaporation rate of Cs-Pb-X at 0.03~0.1 nm / s, and the substrate temperature at 70~120 ℃, to obtain a CsPbX3 structure phase uniformly passivated and encapsulated by the CsZnX3 structure phase.
[0006] The dual-source co-evaporation method specifically includes the following steps: First, CsX and PbX2 are weighed at a molar ratio of 2:1 and ground to obtain a uniformly mixed Cs-Pb-X solid powder; then, using Cs-Pb-X solid powder and ZnX2 as raw materials, a dual-source co-evaporation method is adopted, controlling the evaporation rate ratio of ZnX2 to CsPbX3 at 1:10, the evaporation rate of CsPbX3 at 0.06 nm / s, and the substrate temperature at 100 ℃, to obtain a CsPbX3 structural phase uniformly passivated and encapsulated by the CsZnX3 structural phase.
[0007] The interface-induced assisted thermal annealing method specifically includes the following steps: First, a 2-5 nm thick ZnX2 layer is deposited by vapor deposition. Then, CsX and PbX2 layers are deposited alternately in sequence. There are 3-8 pairs of CsX and PbX2 layers, with the thicknesses of CsX and PbX2 in each pair being 7-11 nm and 3-6 nm, respectively. Then, annealing is performed under nitrogen atmosphere or vacuum atmosphere of 10-2 Pa to 10-4 Pa, with an annealing temperature of 70-120℃ and an annealing time of 20-60 minutes, to obtain a CsPbX3 structure phase uniformly passivated and encapsulated by the CsZnX3 structure phase.
[0008] The interface-induced assisted thermal annealing method specifically includes the following steps: First, a 3 nm thick ZnX2 layer is deposited by vapor deposition. Then, five pairs of CsX and PbX2 layers are deposited alternately by vapor deposition. The thicknesses of CsX and PbX2 in each pair are 8 nm and 4 nm, respectively. Then, annealing is performed under nitrogen or 10-4 Pa conditions at 100°C for 30 minutes to obtain a CsPbX3 structure phase light-emitting layer uniformly passivated by the CsZnX3 structure phase.
[0009] A perovskite luminescent layer is prepared by any of the passivation methods described above.
[0010] A thermally vapor-deposited perovskite LED device includes the aforementioned light-emitting layer.
[0011] A thermally vaporized perovskite LED device, characterized in that it further includes an anode, a hole transport layer, an electron transport layer, and a cathode, wherein the light-emitting layer is located between the hole transport layer and the electron transport layer.
[0012] Compared to existing technologies, this invention utilizes dual-source co-evaporation or interface-induced assisted thermal annealing to construct CsZnX3 as a passivation layer for lead halide perovskite. CsZnX3 not only exhibits a significant passivation effect but also demonstrates superior conductivity compared to conventional Cs4PbX6, thus overcoming the adverse effects of low electrical and electroluminescent properties in LED devices caused by Cs4PbX6 passivation layers. Simultaneously, the introduction of Zn reduces the Pb content in the overall structure of the lead halide perovskite light-emitting layer, mitigating the toxicity of Pb to some extent. Furthermore, both the dual-source co-evaporation and interface-induced preparation methods employed offer good controllability and are simple to operate. Attached Figure Description
[0013] Figure 1 This is a schematic diagram illustrating the formation principle of the CsZnBr3 passivation layer.
[0014] Figure 2 This is a schematic diagram showing the effect of ZnBr2 on the absorption characteristics of the perovskite luminescent layer.
[0015] Figure 3 This is a schematic diagram showing the effect of ZnBr2 on the luminescence properties of the perovskite luminescent layer.
[0016] Figure 4 This is a schematic diagram of the current-voltage characteristics of an LED device including the aforementioned perovskite light-emitting layer.
[0017] Figure 5 This is a schematic diagram of the electroluminescence characteristics of an LED device including the aforementioned perovskite light-emitting layer. Detailed Implementation Example
[0018] The passivation method for perovskite LED light-emitting layer by thermal evaporation using dual-source co-evaporation includes the following steps: First, CsBr and PbBr2 are weighed at a molar ratio of 2:1 and then ground to obtain a uniformly mixed Cs-Pb-Br solid powder. Then, using Cs-Pb-Br solid powder and ZnBr2 as raw materials, a dual-source co-evaporation method was adopted, controlling the evaporation rate ratio of ZnBr2 to Cs-Pb-Br at 1:10, the evaporation rate of Cs-Pb-Br at 0.06 nm / s, and the substrate temperature at 100 ℃, to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase.
[0019] Figure 1 This is a schematic diagram illustrating the formation principle of the CsZnBr3 passivation layer. Figure 1It can be seen that under the action of ZnBr2, the CsPb4Br6 structural phase is suppressed and the CsZnBr3 structural phase is generated, and the CsPbBr3 structural phase is uniformly passivated and encapsulated by the CsZnBr3 structural phase.
[0020] The perovskite luminescent layer prepared by the passivation method described in Example 1 was tested for its absorption and luminescence properties, as shown below. Figure 2 and Figure 3 As shown, by Figure 2 As can be seen, the intensity of the Cs4PbBr6 phase generated from excess CsBr decreases after the addition of ZnBr2, indicating that some CsBr binds to ZnBr2 at this point. Figure 3 It is evident that the fluorescence intensity increased significantly after the addition of ZnBr2, indicating that the passivation effect of CsZnBr3 is significant and superior to that of Cs4PbBr6.
[0021] A thermally vapor-deposited perovskite LED device includes an anode, a hole transport layer, a perovskite light-emitting layer, an electron transport layer, and a cathode, or a cathode, an electron transport layer, a perovskite light-emitting layer, a hole transport layer, and an anode, wherein the perovskite light-emitting layer is prepared by the passivation method described in Example 1.
[0022] The current-voltage characteristics and electroluminescence characteristics of the LED devices prepared above were tested, as shown in the figures below. Figure 4 and Figure 5 As shown, by Figure 4 It can be seen that the current density increases significantly after adding ZnBr2, proving that the electrical properties of the CsZnBr3 passivation layer are significantly better than those of Cs4PbBr6. Figure 5 As can be seen, the device constructed with the CsZnBr3 passivation layer achieves a maximum luminance and EQE of 27863 cd / m². 2 And 7.6%, which is a significant improvement compared to devices passivated by Cs4PbBr6. Example
[0023] The passivation method for perovskite LED light-emitting layer by thermal evaporation using dual-source co-evaporation includes the following steps: First, CsBr and PbBr2 are weighed at a molar ratio of 1.2:1 and then ground to obtain a uniformly mixed Cs-Pb-Br solid powder; Then, using Cs-Pb-Br solid powder and ZnBr2 as raw materials, a dual-source co-evaporation method was adopted, controlling the evaporation rate ratio of ZnBr2 to Cs-Pb-Br at 1:50, the evaporation rate of Cs-Pb-Br at 0.03 nm / s, and the substrate temperature at 70 ℃, to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase. Example
[0024] The passivation method for perovskite LED light-emitting layer by thermal evaporation using dual-source co-evaporation includes the following steps: First, CsBr and PbBr2 are weighed at a molar ratio of 4:1 and then ground to obtain a uniformly mixed Cs-Pb-Br solid powder. Then, using Cs-Pb-Br solid powder and ZnBr2 as raw materials, a dual-source co-evaporation method was adopted, controlling the evaporation rate ratio of ZnBr2 to Cs-Pb-Br at 1:5, the evaporation rate of Cs-Pb-Br at 0.10 nm / s, and the substrate temperature at 120 ℃, to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase. Example
[0025] The passivation method for perovskite LED light-emitting layer by thermal evaporation using dual-source co-evaporation includes the following steps: First, CsBr and PbBr2 are weighed at a molar ratio of 3:1 and then ground to obtain a uniformly mixed Cs-Pb-Br solid powder. Then, using Cs-Pb-Br solid powder and ZnBr2 as raw materials, a dual-source co-evaporation method was adopted, controlling the evaporation rate ratio of ZnBr2 to Cs-Pb-Br at 1:20, the evaporation rate of Cs-Pb-Br at 0.08 nm / s, and the substrate temperature at 80 ℃, to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase.
[0026] The Br element can be replaced with Cl or I from the same group. Example
[0027] The passivation method for perovskite LED light-emitting layer by thermal evaporation using dual-source co-evaporation includes the following steps: First, CsI and PbBr2 are weighed at a molar ratio of 3:1 and then ground to obtain a uniformly mixed Cs-Pb-Br-I solid powder. Then, using Cs-Pb-Br-I solid powder and ZnI2 as raw materials, a dual-source co-evaporation method was adopted. The evaporation rate ratio of ZnI2 to Cs-Pb-Br-I was controlled at 1:20, the evaporation rate of Cs-Pb-Br-I was 0.08 nm / s, and the substrate temperature was 80 ℃, to obtain CsZn(Br) x I 3-x )3 CsPb(Br) structure phase uniformly passivated and encapsulated x I 3-x )3 structural phase. Example
[0028] The passivation method for perovskite LED light-emitting layer by thermal evaporation using dual-source co-evaporation includes the following steps: First, CsCl and PbBr2 are weighed at a molar ratio of 3:1 and then ground to obtain a uniformly mixed Cs-Pb-Cl-Br solid powder. Then, using Cs-Pb-Cl-Br solid powder and ZnCl2 as raw materials, a dual-source co-evaporation method was adopted. The evaporation rate ratio of ZnCl2 to Cs-Pb-Cl-Br was controlled at 1:20, the evaporation rate of Cs-Pb-Cl-Br was 0.08 nm / s, and the substrate temperature was 80℃, to obtain CsZn(Cl x Br 3-x )3 CsPb(Cl) structure phase uniformly passivated and encapsulated x Br 3-x )3 structural phase. Example
[0029] The passivation method for perovskite LED light-emitting layers using interface-induced assisted thermal annealing includes the following steps: First, a 4 nm ZnBr2 layer is deposited by evaporation, followed by alternating deposition of 5 pairs of CsBr and PbBr2 layers, with CsBr and PbBr2 layers having thicknesses of 9 nm and 5 nm respectively in each pair. Then, annealing is performed at 100°C for 30 minutes under nitrogen atmosphere to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase. Example
[0030] The passivation method for perovskite LED light-emitting layers using interface-induced assisted thermal annealing includes the following steps: First, a 2 nm ZnBr2 layer is deposited, followed by alternating deposition of three pairs of CsBr and PbBr2 layers, with CsBr and PbBr2 layers having thicknesses of 7 nm and 3 nm respectively in each pair. Then, annealing is performed under 10 °C conditions. -4 Annealing at 70℃ for 60 minutes under Pa conditions yielded a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase. Example
[0031] The passivation method for perovskite LED light-emitting layers using interface-induced assisted thermal annealing includes the following steps: First, a 5 nm ZnBr2 layer is deposited by evaporation, followed by the alternating deposition of 8 pairs of CsBr and PbBr2 layers, with CsBr and PbBr2 layers having thicknesses of 11 nm and 6 nm respectively in each pair. Then, annealing is performed at 120°C for 20 minutes under nitrogen atmosphere to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase. Example
[0032] The passivation method for perovskite LED light-emitting layers using interface-induced assisted thermal annealing includes the following steps: First, a 3 nm ZnBr2 layer is deposited by evaporation, followed by alternating deposition of 6 pairs of CsBr and PbBr2 layers, with CsBr and PbBr2 layers having thicknesses of 9 nm and 4 nm in each pair, respectively. Then, annealing is performed at 90°C for 50 minutes under nitrogen atmosphere to obtain a CsPbBr3 structure phase uniformly passivated and encapsulated by the CsZnBr3 structure phase.
[0033] The Br element can be replaced with Cl or I from the same group. Example
[0034] A passivation method for perovskite LED light-emitting layers using interface-induced assisted thermal annealing includes the following steps: First, a 4 nm ZnI2 layer is deposited. Then, five pairs of CsBr and PbI2 layers are deposited alternately, with CsBr and PbI2 layers having thicknesses of 8 nm and 5 nm respectively in each pair. Annealing is then performed at 100°C for 60 minutes under nitrogen atmosphere to obtain a perovskite LED light-emitting layer composed of CsZn(Br) x I 1-x )3 CsPb(Br) structure phase uniformly passivated and encapsulated x I 1-x )3 structural phase. Example
[0035] A passivation method for perovskite LED light-emitting layers using interface-induced assisted thermal annealing includes the following steps: First, a 4 nm ZnCl2 layer is deposited. Then, five pairs of CsBr and PbCl2 layers are deposited alternately, with CsBr and PbCl2 layers having thicknesses of 8 nm and 4 nm respectively in each pair. Annealing is then performed at 90°C for 30 minutes under nitrogen atmosphere to obtain a perovskite LED light-emitting layer composed of CsZn(Br) x Cl 1-x )3 CsPb(Br) structure phase uniformly passivated and encapsulated x Cl 1-x )3 structural phase.
[0036] Compared with the prior art, the present invention can achieve the following beneficial effects: Compared to Cs4PbBr6 passivation layer, CsZnBr3 achieves high-quality passivation while also possessing excellent conductivity. This not only improves the luminous efficiency of the lead halide perovskite light-emitting layer but also takes into account the current characteristics of the LED device, ultimately significantly enhancing the device performance of thermally vaporized perovskite LEDs.
[0037] The introduction of ZnBr2 can form a passivation phase through the following reaction: ZnBr2 + CsBr (excess during evaporation) → CsZnBr3. On the one hand, it can prevent PbBr2 from further converting to Cs4PbBr6 with poor conductivity through PbBr2 + CsBr → Cs4PbBr6. On the other hand, it can also effectively reduce the Pb content in the overall structure of the light-emitting layer, thereby overcoming the influence of Pb toxicity to a certain extent.
[0038] The preparation method using dual-source co-evaporation or interface-induced bonding followed by annealing can effectively avoid the complex control of triple-source co-evaporation of PbBr2, CsBr, and ZnBr2, while retaining the process advantages of dual-source co-evaporation in terms of controllability, uniformity, and large area.
[0039] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several changes and improvements without departing from the overall concept of the present invention, and these should also be considered within the scope of protection of the present invention.
Claims
1. A passivation method for thermally deposited perovskite LED light-emitting layers, characterized in that: CsZnX3 structural phase uniformly passivated and encapsulated CsPbX3 structural phase was prepared by dual-source co-evaporation or interface-induced assisted thermal annealing, wherein X is one or two of Br, Cl or I. The dual-source co-distillation method specifically includes the following steps: First, CsX and PbX2 are weighed at a molar ratio of 1.2-4:1 and then ground to obtain a uniformly mixed Cs-Pb-X solid powder. Then, using Cs-Pb-X solid powder and ZnX2 as raw materials, a dual-source co-evaporation method was adopted, controlling the evaporation rate ratio of ZnX2 to Cs-Pb-X at 1:50 to 1:5, the evaporation rate of Cs-Pb-X at 0.03 to 0.1 nm / s, and the substrate temperature at 70 to 120 °C, to obtain a CsPbX3 structure phase uniformly passivated and encapsulated by the CsZnX3 structure phase; The interface-induced assisted thermal annealing method specifically includes the following steps: First, a 2-5 nm thick ZnX2 layer is deposited by vapor deposition. Then, CsX and PbX2 layers are deposited alternately in sequence, with 3-8 pairs of CsX and PbX2 layers. The thicknesses of CsX and PbX2 in each pair are 7-11 nm and 3-6 nm, respectively. Annealing is then performed under nitrogen atmosphere or vacuum conditions of 10 °C. -2 Pa~10 -4 Under Pa conditions, the annealing temperature is 70-120℃ and the annealing time is 20-60 minutes to obtain a CsPbX3 structure phase uniformly passivated and encapsulated by the CsZnX3 structure phase.
2. The passivation method for a thermally evaporated perovskite LED light-emitting layer according to claim 1, characterized in that: In the dual-source co-evaporation method, the molar ratio of CsX and PbX2 is 2:1, the dual-source evaporation rate ratio of ZnX2 to CsPbX3 is 1:10, the evaporation rate of CsPbX3 is 0.06 nm / s, and the substrate temperature is 100 ℃.
3. The passivation method for a thermally evaporated perovskite LED light-emitting layer according to claim 1, characterized in that: In the interface-induced assisted thermal annealing method, the ZnX2 thickness is 3 nm, and there are 5 pairs of CsX and PbX2 layers. The thicknesses of CsX and PbX2 in each pair are 8 nm and 4 nm, respectively. The annealing conditions are nitrogen or 10 -4 Anneal at 100°C for 30 minutes under Pa conditions.
4. A perovskite luminescent layer, prepared by the passivation method described in any one of claims 1-3.
5. A thermally vapor-deposited perovskite LED device, characterized in that: Includes the light-emitting layer as described in claim 4.
6. The thermally vaporized perovskite LED device according to claim 5, characterized in that: It also includes an anode, a hole transport layer, an electron transport layer, and a cathode, with the light-emitting layer located between the hole transport layer and the electron transport layer.
Citation Information
Patent Citations
Lead-doped zinc-based halide nano luminescent material as well as preparation method and application thereof
CN114605987A
Copper-zinc-tin-sulfur thin-film solar cell light absorption layer and preparation method thereof, and copper-zinc-tin-sulfur thin-film solar cell
CN114784138A
